Serum creatine-kinase and extended breastfeeding: Case study - Ksenija Bubnjević; Bojana Marić; Dušan Stupar; Dragan Grujičić (Exercise and Quality of Life, 2022)
The World Health Organization recommends infants should be exclusively breastfed for the first six months of life. Various factors can affect the maintenance of lactation. Increased physical activity and stress are thought to negatively affect breastfeeding success. The aim of this case study was to examine the effect of high serum creatine-kinase (CK) values and the success of breastfeeding after sports competition. It is assumed that continuous aerobic exercise is a stress for the body that can have a negative impact on lactation and extended breastfeeding. Methods. The level of acute muscle damage (AC) was measured before and after the competition in order to confirm continuous exposure to aerobic exercise. Results. After the competition, elevated serum creatine-kinase levels were noted. Prolactin and TSH values remained within optimal values. Conclusion. Several months of preparation for the competition had an impact on increasing acute muscle damage (AC) after the competition. No negative effect of continuous aerobic exercise on breastfeeding success was observed in this case study.